The relative importance of factors influencing the adoption of sustainable agricultural practices: a factor approach for Malaysian vegetable farmers - Tey, Yeong Sheng; Li, Elton; Bruwer, Johan; Abdullah, Amin Mahir; Brindal, Mark Kennion; Radam, Alias; Ismail, Mohd Mansor; Darham, Suryani (Springer, 2014)
This study develops the understanding of the adoption of sustainable agricultural practices (SAPs) by investigating the relative importance of a set of multidimensional factors in the Malaysian vegetable production sector. A factor approach is deployed to identify explanatory indicators within an integrative framework that is synthesized from the theory of interpersonal behavior and the theory of diffusion of innovation. We achieved this by analyzing a logistic regression model for the adoption of six individual SAPs (conservation tillage, intercropping, cover crops/mulches, crop rotation, organic fertilizers/composts, and integrated pest management). The findings indicate that adoption depends on a range of socio-economic, agro-ecological, institutional, informational, and psychological factors, as well as the perceived attributes of SAPs. Fundamental policy understanding of the issue should, therefore, be multidisciplinary. In addition, standardized coefficients reveal that the impact of statistically significant factors on adoption is unequal. In general, the most influential factor is the asymmetric distribution of resources across geographical locations. This is followed by financial capital and a number of factors, including the workforce size, the usefulness of information, Chinese ethnicity, and the perceived relative advantage of SAPs. Guided by this prioritization understanding, future SAPs promotion now has a better opportunity to target the more important areas. Similar research effort should be made to steer sustainable agriculture internationally.